Problems and Prospects of Risk Insurance in Tourism Activities in Transition Economies (Based on the experience of Uzbekistan) - Azimov, Rustam Sadykovich; Mirsadikov, Miradil; Abdullaev, Abdulaziz (Transactions on Engineering and Computing Sciences, 2025)
In the context of globalization and interstate integration, the concept of advanced tourism development is becoming one of the key areas for ensuring the sustainable economic growth of a country. An important aspect of this concept is the introduction of effective and accessible insurance protection mechanisms for both tourists and tourism organizations. The growth of global and domestic tourism is accompanied by an increased level of economic, socio-political, and environmental risks, which can significantly affect tourism activity and participants in the tourism market. The issues and prospects of risk insurance in the tourism sector remain insufficiently studied in both domestic and global economic science. This study aims to identify key problems and development prospects for insurance in the tourism sector of the Republic of Uzbekistan, which will help to develop effective strategies for minimizing risks and supporting the sustainable development of the country's tourism sector.